Shelter in a Time of Storm : How Black Colleges Fostered Generations of Leadership and Activism - Favors, Jelani Manu-Gowon, 1975- (Book collections on Project MUSE., 2019)
"For generations, Black colleges have been essential institutions for the African American community. Their nurturing environments have not only aided in students' education and advancement. They have also offered spaces to develop racial consciousness and analyze the paradoxes embodied in American culture. The development and politicization of students on the campuses of historically Black colleges and universities (HBCUs) has resulted in waves of activism, catalyzing the modern Civil Rights Movement and forever altering the political destiny of the United States"--